Excited negative parity bands in 160Yb. (29th January 2018) - Saha, A; Bhattacharjee, T; Curien, D; Dedes, I; Mazurek, K; Banerjee, S R; Rajbanshi, S; Bisoi, A; Angelis, G de; Bhattacharya, Soumik; Bhattacharyya, S; Biswas, S; et al.
Abstract: Negative parity rotational bands in 70 160 Yb 90 nucleus have been studied. They were populated in the 148 Sm( 16 O, 4n) 160 Yb reaction at 90 MeV. The gamma-coincidence data have been collected using Indian National Gamma Array composed of twenty Compton suppressed clover germanium (Ge) detectors. Double gating on triple gamma coincidence data were selectively used to develop the decay scheme for these negative parity bands by identifying and taking care of the multiplet transitions. The even- and odd-spin negative parity bands in 160 Yb have been studied by comparing the reduced transition probability ratios with the similar bands in neighbouring even–even rare earth nuclei. It is concluded that the concerned odd-spin and even-spin bands are not signature partners and that their structures are compatible with those of the 'pear-shape' and 'pyramid-shape' oscillations, respectively, the octupole shapes superposed with the quadrupole shape of the ground-state.